Sistem Infomasi Persebaran Hewan Ternak Sapi, Domba dan Kambing di Wilayah Kerja UPT IV Dinas Perikanan dan Peternakan Kabupaten Bogor Berbasis WEBGIS - Anara, Faisal Fakhri; Hermawan, Erwin; Karmilah, Nurul (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
One of the policies of the Bogor Regency Livestock and Fisheries Office is to promote livestock production and develop an integrated and comprehensive information system on the distribution of livestock populations in each sub-district of Bogor Regency to the community. This WEBGIS-based information system on the distribution of livestock in each area was created to support the policies of the Bogor Regency Livestock and Fisheries Service and to make it easier for people who want to know the development of the livestock population in Bogor Regency and see which areas have the potential for the production of cattle, goats and sheep. in a particular area. The problem limitation in this study only covers cattle, sheep and goats in the working area of the UPT IV Fisheries and Livestock Service Office of Bogor Regency which covers Dramaga, Ciomas, Tamansari, Caringin, Cigombong and Cijeruk Districts, with data on the number of population distribution of livestock obtained from in 2018 and 2019. Then an information system for the distribution of livestock was made in the 6 sub-districts of the UPT IV UPT Department of Fisheries and Livestock IV, Bogor Regency based on WEBGIS. The implementation of the information system developed through WEBGIS is able to present information in the form of graphs and tables per type of livestock, per district and per year. Presenting a map of the distribution of livestock population with color degradation, as well as presenting the location points of the distribution of livestock per village. Based on this, it is possible to know the stock of livestock in each area so that the Bogor Animal Husbandry and Fisheries Agency can estimate the level of livestock production in order to meet the community’s need for meat.